Mechanical Properties of Durian/Luffa Fiber Reinforced Polymer Composite - Mohd Khairul, Afiq; Nicholas Kuan, Hoo Tien; Christopher Joyle, Indor (Trans Tech Publications Ltd., 2025)
Abstract: This research explores the development of advanced materials known as natural fiber reinforced polymer (FRP) composites with the aim of enhancing overall quality of life. Hybrid fibers derived from durian/luffa fibers were integrated into Polyethylene (PE) matrices to fabricate hybrid natural fiber PE composites. The study involves a comprehensive examination of these composites through tensile testing, scanning electron microscopy (SEM), and Fourier-Transform Infrared (FTIR) analysis. Results indicate that the tensile strength of the durian/luffa PE (DLPE) composite surpasses that of neat PE laminates, highlighting its superior stress tolerance. Overall, the composites exhibit specific tensile strength and modulus, contributing to the creation of lightweight materials compared to neat PE. SEM analysis indicates satisfactory fiber-to-matrix bonding with room for improvement, as observed gaps between fibers and matrix are present. FTIR analysis uncovers constituents in the chemical composition of durian and luffa fibers. The inclusion of natural fibers as an alternative to synthetic counterparts aligns with Sustainable Development Goals (SDG) standards. This research underscores the feasibility and benefits of fiber hybridization, emphasizing improved mechanical strength, environmental sustainability, and cost efficiency.